2007
DOI: 10.1143/jpsj.76.043201
|View full text |Cite
|
Sign up to set email alerts
|

Experiment on Synthesis of an Isotope 277112 by 208Pb+70Zn Reaction

Abstract: The production and decay of 277 112 have been investigated using a gas-filled recoil ion separator in irradiations of 208 Pb targets with a 70 Zn beam at 349.5 MeV. We have observed two -decay chains that can be assigned to subsequent decays from 277 112 produced in the 208 Pb( 70 Zn,n) reaction. After emitting four consecutive -particles, both the chains terminate by spontaneous fission decays of 261 Rf, and the decay energies and decay times of both the chains obtained in the present work agree well with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(117 citation statements)
references
References 17 publications
2
115
0
Order By: Relevance
“…JWP ASSESSMENT: The 1996 collaboration of Hofmann et al [5] combined with the 2002 collaboration of Hofmann et al [6] are accepted as the first evidence for the synthesis of element with atomic number 112, being supported by subsequent measurements of Morita et al [16,18], and by assignment of decay properties of likely hassium intermediates [9,11,13] in the decay chain originating from 277 112. tion studies using multi-GeV protons incident on a U target clearly indicated the production path was irreproducible as previously stressed [1,3,4]. The latter refutations have been challenged by Brandt [18,25], a member of the Marinov collaboration, in which he rejects the negative results because the same exact experiment as conducted by Marinov was not followed.…”
Section: Discovery Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…JWP ASSESSMENT: The 1996 collaboration of Hofmann et al [5] combined with the 2002 collaboration of Hofmann et al [6] are accepted as the first evidence for the synthesis of element with atomic number 112, being supported by subsequent measurements of Morita et al [16,18], and by assignment of decay properties of likely hassium intermediates [9,11,13] in the decay chain originating from 277 112. tion studies using multi-GeV protons incident on a U target clearly indicated the production path was irreproducible as previously stressed [1,3,4]. The latter refutations have been challenged by Brandt [18,25], a member of the Marinov collaboration, in which he rejects the negative results because the same exact experiment as conducted by Marinov was not followed.…”
Section: Discovery Profilesmentioning
confidence: 99%
“…The latter refutations have been challenged by Brandt [18,25], a member of the Marinov collaboration, in which he rejects the negative results because the same exact experiment as conducted by Marinov was not followed. However, independent evidence is what "Criteria" (q.v.)…”
Section: Discovery Profilesmentioning
confidence: 99%
“…A detailed presentation and discussion of the GSI-SHIP results on the decay properties of elements 107 to 112 was given in previous reviews [15,38,39]. The results of experiments at RIKEN on the confirmation of elements 110 to 112 and the first production of an isotope of element 113 using a cold fusion reaction were published in [40][41][42][43][44]. A systematic work on cold fusion reactions aiming to study the influence of neutron number and of target-projectile asymmetry on the cross-section was performed at LBNL.…”
Section: New Elements Made By Cold-fusion Reactionsmentioning
confidence: 99%
“…Decay chains measured in the cold fusion reaction 70 Zn + 208 Pb → 278 112 * . In the left part the two chains are shown, which were measured in 1996 and 2000 at SHIP [25,76], in the right part those measured in 2004 at RIKEN [43]. The chains were assigned to the isotope 277 112 produced by evaporation of one neutron from the compound nucleus.…”
Section: Element 112 Coperniciummentioning
confidence: 99%
“…In the "cold" fusion reactions based on the closed shell target nuclei, lead and bismuth, SH elements up to Z = 113 have been produced [1,2]. The "world record" of 0.03 pb in production cross section of 113 element has been obtained here within more than half-year irradiation of 209 Bi target with 70 Zn beam [2]. Further advance in this direction (with Ga or Ge beams) seems to be very difficult.…”
Section: Introductionmentioning
confidence: 96%